Sleep difficulties and disorders in Autism Spectrum Disorder - Richdale, Amanda L.; Johnson, Kyle P. (Emerald Publishing Limited : Information Age Publishing, inc., 2020)
"Sleep problems are highly prevalent in autism spectrum disorder (ASD) with evidence suggesting that majority of these children will experience a sleep problem at some point. Sleep problems in ASD are often chronic, and are associated with more severe child behaviour difficulties, anxiety, and ADHD symptoms. Mothers of children with sleep problems experience disturbed sleep, more stress and poorer psychological well being. Most commonly parents report their children to have difficulties with settling and night waking which are often amenable to behavioural treatment or melatonin. Nevertheless other sleep issues such as short night sleep, early waking, extended periods of night waking, early waking and circadian sleep disturbances are also reported and can be difficult to treat. While there is now a considerable body of evidence to support that those with ASD can experience significant and sometimes debilitating sleep difficulties, there is little research on the aetiology, prevention or intervention. This book brings together current research and clinical experience by experts from North America, UK, Europe and Australasia regarding the behavioural and medical factors that might underlie these prevalent sleep difficulties, as well as both medical and behavioural approaches to treatment. The book has three major section Aetiological factors and Diagnosis which covers the impacts of ASD on sleep, comorbid medical and psychiatric conditions, and diagnostic tools; Impact of Sleep Problems covering both the child and their family; and Treatment, including pharmacological and behavioural treatments, and the usefulness or otherwise of alternative treatments. This book will be useful for clinicians and researchers with an interest in ASD and paediatric sleep"-- Provided by publisher.
Keywords: Sleep disorders in children.; Sleep disorders in children -- Treatment.; Autism spectrum disorders.; Psychology -- Psychopathology -- Autism Spectrum Disorders.; Sleep disorders and therapy.; Autism and Aspergers Syndrome.; elektronické knihy; electronic books